Re-evaluating conservation priorities of New World tarantulas (Araneae: Theraphosidae) in a molecular framework indicates non-monophyly of the genera, Aphonopelma and Brachypelma. Issue 1 (2nd January 2018) - Turner, Steven P.; Longhorn, Stuart J.; Hamilton, Chris A.; Gabriel, Ray; PÉrez-Miles, Fernando; Vogler, Alfried P.
Abstract : We present a mtDNA gene tree of tarantula spiders (Araneae: Mygalomorphae: Theraphosidae) based on the mitochondrial 16S-tRNA (leu)-ND1 gene region as a promising initial molecular hypothesis to clarify the taxonomy of the largest subfamily, Theraphosinae. Many species of this New World subfamily are traded widely as exotic pets, yet few scientific studies on them exist, and the robustness of many supposed taxonomic groupings is debatable. Yet the validity of taxon names and knowledge of their distinctiveness is vital for trade regulation, most notably for the Neotropical genus Brachypelma Simon 1891, which is listed under CITES (Appendix II, see online supplemental material, which is available from the article's Taylor & Francis Online page athttps://doi.org/10.1080/14772000.2017.1346719 ). The use of molecular markers for tarantula taxonomy has been limited until recently, with most previous studies relying on morphological methods. Our findings, from newly collected molecular data, have several nomenclatural implications, suggesting a need for a rigorous overhaul of Theraphosinae classification at multiple hierarchical levels. Here, we take steps toward a revised classification, favouring division of Theraphosinae into three tribes: the Theraphosini trib. nov., the Hapalopini trib. nov., and the Grammostolini trib. nov. We also make conservation recommendations for two non-monophyletic genera. Firstly, we recover Aphonopelma Pocock 1901 as polyphyletic, finding that the large radiation into the USA and Mexico is taxonomically distinct from at least three other lineages distributed throughout Central America, one of which includes the type species of the genus. Secondly, and importantly for conservation, we find diphyly in the CITES listed genus Brachypelma Simon 1891, where our data strongly favour a division into two distinct smaller genera. We consider only the lineage with endemics in the Pacific coastal zone of Mexico to be of conservation concern. Finally, we also make suggestions on the future direction of revisionary research for the Theraphosidae as a whole. http://zoobank.org/urn:lsid:zoobank.org:pub:B37F7795-3F92-4334-A0C7-65C8026EE1FB